Half-metallicity in organic single porous sheets - Kan, Erjun (2013)
The unprecedented applications of two-dimensional (2D) atomic sheets in spintronics are formidably hindered by the lack of ordered spin structures. Here we present first-principles calculations demonstrating that the recently synthesized dimethylmethylene-bridged triphenylamine (DTPA) porous sheet is a ferromagnetic half-metal and that the size of the band gap in the semiconducting channel is roughly 1 eV, which makes the DTPA sheet an ideal candidate for a spin-selective conductor. In addition, the robust half-metallicity of the 2D DTPA sheet under external strain increases the possibility of applications in nanoelectric devices. In view of the most recent experimental progress on controlled synthesis, organic porous sheets pave a practical way to achieve new spintronics.